2021
DOI: 10.3389/fpls.2020.602313
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Detailed Characterization of Transgene Insertion Sites in Genetically Modified Plants via Nanopore Sequencing

Abstract: Molecular characterization of genetically modified plants can provide crucial information for the development of detection and identification methods, to comply with traceability, and labeling requirements prior to commercialization. Detailed description of the genetic modification was previously a challenging step in the safety assessment, since it required the use of laborious and time-consuming techniques. In this study an accurate, simple, and fast method was developed for molecular characterization of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Osamu et al identified a single transgene insertion and confirmed a large genomic deletion during transgene insertion in a transgenic mouse strain (Suzuki et al, 2020). Paula et al reported the molecular characterization of three GM plant species using MinION at the WGS level (Giraldo et al, 2021). Anne-Laure et al identified genomic insertion and flanking sequences in transgenic drought-tolerant maize line 'SbSNAC1-382' using single-molecule real-time (SMRT) sequencing coupled with plasmid rescue (Boutigny et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osamu et al identified a single transgene insertion and confirmed a large genomic deletion during transgene insertion in a transgenic mouse strain (Suzuki et al, 2020). Paula et al reported the molecular characterization of three GM plant species using MinION at the WGS level (Giraldo et al, 2021). Anne-Laure et al identified genomic insertion and flanking sequences in transgenic drought-tolerant maize line 'SbSNAC1-382' using single-molecule real-time (SMRT) sequencing coupled with plasmid rescue (Boutigny et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Paula et al . reported the molecular characterization of three GM plant species using MinION at the WGS level (Giraldo et al ., 2021 ). Anne‐Laure et al .…”
Section: Introductionmentioning
confidence: 99%
“…To date, progeny testing ( McHugh et al, 2012 ), quantitative Southern blotting analysis ( Stumpel et al, 2018 ), fluorescent in situ hybridization ( McHugh et al, 2012 ), direct fluorescence imaging ( Lin et al, 2015 ), and quantitative PCR (qPCR) assay ( Tesson et al, 2010 ) are commonly used methods to discriminate homozygous from heterozygous transgenic mice. Computation biology-based methods such as Illumina whole genome sequencing ( Yong et al, 2015 ; Irie et al, 2017) , nanopore sequencing ( Giraldo et al, 2020 ), Xdrop indirect sequencing (Samplix) ( Blondal et al, 2021 ), and nanopore adaptive sampling ( Ulrich et al, 2022 ) have recently demonstrated their abilities in determination of transgene zygosity. However, these methods are either time-consuming, or require knowledge and capability of biological computation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite conducting a bioinformatics analysis of that flanking sequence, it was still difficult to determine the insert position of SK12-5 by using the conventional methods. To overcome this problem, in this study, the combined methods of genetic mapping (Zhang et al, 2015 , and Michelmore et al, 1991 ) and nanopore-based sequencing technology (Giraldo et al, 2020 ) were applied to further analyze the insertion position of SK12-5. The findings of this study are therefore very helpful for understanding the molecular characterization of SK12-5.…”
Section: Introductionmentioning
confidence: 99%